Method-dependent differences in VO2 peak determination and their implications for percentage-based exercise prescription in elite rowers - Chen, S.; Zhang, Y.; Li, X.; Liu, Y.; Yang, S.; Zhang, X.; Liang, W. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Purpose Precise determination of peak oxygen uptake (VO2peak) is important for athlete profiling and exercise prescription. However, common data-processing approaches applied to breath-by-breath gas-exchange data may yield different VO2peak values, particularly in elite athletes with high ventilatory rates. This study compared three commonly used VO2peak determination methods and quantified their impact on percentage-based exercise prescription in national-level rowers.